Nilai-Nilai Pendidikan dalam Prosesi Ritual Adat Keboan Desa Aliyan Kecamatan Rogojampi Kabupaten Banyuwangi - Erna Nur Hidayah; Setya Yuwana; Trisakti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to dissect the educational values ​​contained in the four processions in the Keboan traditional ritual for the younger generation and the wider community. This research uses descriptive qualitative research using a case study approach, namely with the aim of explaining and providing an overview of events in the field. The research results reveal that each procession has a different meaning and has different educational values ​​even though the four Keboan traditional ritual processes have the same goal. The four processions in the Keboan traditional ritual of Aliyan village contain religious education values, social education values ​​and cultural education values. With several educational values ​​contained in each procession, it can be used as a lesson for the wider community, especially for the younger generation who will inherit these customs and traditions so that the Keboan traditional ritual in Aliyan village continues to exist and is preserved without reducing its sacredness.